(untitled) (Journal of actual problems of jurisprudence, 2022)
In this study, the authors analyze and consider the concept, its legal and methodological aspects, the structure and internal content of environmental law and order, which is one of the main elements enshrined in the basic law of the country. In the epoch of the Anthropocene, environmental legislation and management in the sphere of interaction between society and nature are quite naturally changing. The authors believe that in the new realities of the changing dynamics of environmental management, the role of studying the legal content and structure of environmental law and order is especially relevant. The problems of national environmental legislation, its relevance, timeliness and the necessary coverage of regulatory norms, relevant public relations raises some questions. Such as, and how effective is the social, legal provision of environmental safety in the new realities of environmental threats. For example, environmental man-made disasters, natural disasters caused by global warming, the greenhouse effect, a sharp deterioration in the quantitative and qualitative state of atmospheric air, the ongoing pollution of the oceans and water resources in general, the shortage of drinking water and, significantly, global depletion and the real threat of pollution of the earth. In this regard, we can conclude that there is a "paradigm shift" both in national environmental legislation and in the theoretical aspects of environmental law, the state-legal mechanism of management, and also recognizes the need for a new role in environmental legislation and in the theoretical aspects of environmental law, allowing it to quickly and effectively meet the new dynamics of the changing context of environmental law. There is an urgent need at the present stage of development to increase the growing level of ecological legal awareness of the individual as an element of ecological law and order. Keywords: environmental law, environmental awareness, environmental law and order, environmental protection, environmental education.